Pengaruh Lama Inokulasi dan Ukuran Larva Chilo sacchariphagus Boj. (Lepidoptera: Crambidae) Untuk Perbanyakan Sturmiopsis inferens Towns. (Diptera: Techinidae) di Laboratorium - citra maharani; maryani cyccu tobing; syahrial oemry (Jurnal Agroekoteknologi, 2016)
The objective of the research was to study the inoculation period and larvae size of Chilo sacchariphagus for mass rearing of Sturmiopsis inferens. The research was conducted  in laboratory of Sugarcane Reasearch and Devolopment Sei Semayang  Binjai, Medan, North Sumatera from September until October 2014 using a randomized complete design with two factors and three replications. The first factor was inoculation periods (5, 10, and 15 minutes) and the second factor was larvae sizes of  C. sacchariphagus (< 1.5, 1.5 - 2 and > 2 cm). The results showed that inoculation period and larvae size significantly effected the percentage of parasititation and total of pupa.  The highest percentage of parasititation (4,63 %) on inoculation period for 5 minutes with larvae size > 2 cm and the lowest (0.71 %) on inoculation period for 10 minutes with larvae size < 1.5 cm. The highest total of pupal (2.61 pupal) on inoculation period for 5 minutes with larvae size > 2 cm and the lowest (0.71 pupal) on inoculation period for 10 minutes with larvae size < 1.5 cm. The highest percentage of pupal  to become imago (92.5 %) on larvae size > 2 cm and the lowest (7.5 %) on larvae size < 1.5 cm  and sex ratio of male and female S. inferens is 1 : 1.2.